Exportación de productos artesanales elaborados por personas recluidas en instituciones carcelarias (2021)
Inside the national territory of our Colombian republic, there are a variety of situations that requires proper attention to solve the problems that mainly affect us, these can be economic, political, social, among others, being one of the most affected sectors is the related to the economy, which can trigger another series of problems that require immediate solutions, since they can affect in some way the manner in which the habitants of the country can have better conditions guaranteed by the state. At this point is where this project covers realization, to undertake actions or export projects, prior analyzes are required to determine how viable and profitable these processes can become if they occur. Therefore, this project aims to be an analytical export test model, in which the possibility of exporting products made in Colombian prisons through a penitentiary center and a specific product is analyzed, which suggests how to apply it in another type of products and prisons, through the analysis of specific elements, such as legality, the market, associated institutions, financial and foreign trade concepts, and elements of the penitentiary centers that can develop this management and the way that they must also carry it out, in-house or by outsourcing, thus allowing, in addition to viability, the appropriate profitability and rewarding you for investment and resources. Thus, it is intended to open the door to alternative solutions that allow an improvement of the country's conditions and that additionally allow to prevent or avoid that the economic conflicts that may exist do not have a terrible effect on society, and that for economic conditions of stability, be a reinforcement for improvement, this is how a place is potentiated where there is not much hope of production so that a product "Made in Colombian Jails" becomes an advance for the inhabitants and their nation.